Kajian Feminisme dalam Cerpen ‘Perempuan yang Memanggul Bayangan’ Karya Ferena Debivena - Muhammad Rafli Chudori; Devi Bunga Anggreani; Ahmad Supena (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study uses a feminist literary criticism approach to analyze Ferena Debivena's short story “The Woman Who Bears the Shadow.” To investigate the type of gender inequality experienced by Lara, the main character, this research focuses on three schools of feminism: marxist, social, and liberal. The research used a descriptive qualitative approach, which involved text analysis of the symbolism and narrative structure of the story. The results show that Lara is portrayed as a woman who faces social and emotional challenges due to economic pressure and patriarchal domination. In addition, the short story criticizes forced marriage and educational injustice for women. Despite the strength of its theme, this short story can still be improved by the elements of deepening supporting characters, a clear plot, and strengthening the climax. Therefore, it shows the social reality and serves as a medium to criticize the system that oppresses women.